Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Seasonal variation in cuckoldry rates in the socially monogamous cichlid fish Variabilichromis moorii - Holger Zimmermann; Aneesh P. H. Bose; Helgit Eisner; Jonathan M. Henshaw; Angelika Ziegelbecker; Florian Richter; Sandra Bračun; Cyprian Katongo; Karoline Fritzsche; Kristina M. Sefc (Hydrobiologia, 2023)
Mating patterns in animal populations can respond to environmental conditions and consequently vary across time. To examine this variation in nature, studies must include temporal replicates from the same population. Here, we report temporal variation in genetic parentage in the socially monogamous cichlid Variabilichromis moorii from Lake Tanganyika, using samples of broods and their brood-tending parents that were collected across five field trips from the same study population. The sampled broods were either spawned during the dry season (three field trips) or during the rainy season (two trips). In all seasons, we detected substantial rates of extra-pair paternity, which were ascribed to cuckoldry by bachelor males. Paternity shares of brood-tending males were consistently higher, and the numbers of sires per brood were consistently lower, in broods that were spawned in the dry seasons compared to broods from the rainy seasons. In contrast, the strength of size-assortative pairing in our V. moorii population did not vary temporally. Seasonal fluctuations in environmental conditions, such as water turbidity, are proposed as a mechanism behind variable cuckolder pressure. Our data demonstrate the utility of long-term monitoring to improve our understanding of animal mating patterns.

Brood‐tending males in a biparental fish suffer high paternity losses but rarely cuckold - Aneesh P. H. Bose; Holger Zimmermann; Jonathan M. Henshaw; Karoline Fritzsche; Kristina M. Sefc (Molecular Ecology, 2018)
Extra‐pair paternity within socially monogamous mating systems is well studied in birds and mammals but rather neglected in other animal taxa. In fishes, social monogamy has evolved several times but few studies have investigated the extent to which pair‐bonded male fish lose fertilizations to cuckolders and gain extra‐pair fertilizations themselves. We address this gap and present genetic paternity data collected from a wild population of Variabilichromis moorii , a socially monogamous African cichlid with biparental care of offspring. We show that brood‐tending, pair‐bonded males suffer exceptionally high paternity losses, siring only 63% of the offspring produced by their female partners on average. The number of cuckolders per brood ranged up to nine and yet, surprisingly, brood‐tending males in the population were rarely the culprits. Brood‐tending males sired very few extra‐pair offspring, despite breeding in close proximity to one another. While unpaired males were largely responsible for the cuckoldry, pair‐bonded males still enjoyed higher fertilization success than individual unpaired males. We discuss these results in the context of ecological and phenotypic constraints on cuckoldry and the fitness payoffs of alternative male tactics. Our study provides new insights into how pair‐bonded males handle the trade‐off between securing within‐pair and extra‐pair reproduction.

Seasonal adaptation of dwarf hamsters (Genus Phodopus): differences between species and their geographic origin - D. Müller; J. Hauer; K. Schöttner; P. Fritzsche; D. Weinert (Journal of Comparative Physiology B, 2015)

Characterisation and migration properties of silicone materials during typical long-term commercial and household use applications: a combined case study - R. Helling; P. Seifried; D. Fritzsche; T.J. Simat (Food Additives & Contaminants: Part A, 2012)

Foraging behavior of golden hamsters (Mesocricetus auratus) in the wild - S. C. Larimer; P. Fritzsche; Z. Song; J. Johnston; K. Neumann; R. Gattermann; M. E. McPhee; R. E. Johnston (Journal of Ethology, 2011)

Arsenic Transformation by Azospirillum Brasilense Sp245 in Association with Wheat (Triticum Aestivum L.) Roots - Yelena V. Lyubun; Andreas Fritzsche; Marina P. Chernyshova; E. Gert Dudel; Evgenii E. Fedorov (Plant and Soil, 2006)